1993
DOI: 10.1111/j.1365-2559.1993.tb00499.x
|View full text |Cite
|
Sign up to set email alerts
|

HMB‐45 in non‐melanocytic tumours

Abstract: Brief reports 4 7 7ruled out because of the absence of invasive glands and cytological atypia. The differential diagnosis can be more difficult with inflammatory fibrosarcoma, which, on some occasions, has been called inflammatory pseudo-tumour3. The present case lacked the cellularity and the pleomorphic nuclei with prominent nucleoli commonly seen in inflammatory fibrosarcoma. Moreover, the pancrease was not affected in any of the cases described by Meis and Enzinger in their review of this entity3. Malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 3 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…also observed Melan‐A positivity in these tumours 15 . From a practical point of view it is important that sarcomas are generally HMB‐45‐negative, although there are some observations on HMB‐45‐positive MPNSTs 16 . In the observed series two poorly differentiated GISTs revealed HMB‐45 positivity, even if the specificity of the reaction can be questionable.…”
Section: Discussionmentioning
confidence: 75%
“…also observed Melan‐A positivity in these tumours 15 . From a practical point of view it is important that sarcomas are generally HMB‐45‐negative, although there are some observations on HMB‐45‐positive MPNSTs 16 . In the observed series two poorly differentiated GISTs revealed HMB‐45 positivity, even if the specificity of the reaction can be questionable.…”
Section: Discussionmentioning
confidence: 75%
“…HMB-45 was initially considered a monoclonal antibody that binds to an antigen common to the cytoplasm of melanoma cells and of premature developing melanocytes [16]. Other researchers tested this antibody on various tissues and neoplasms, and concluded that it very rarely stains nonmelanocytic tumors [17]. Kikuchi et al [18] demonstrated that the HMB-45 binding site was mainly the stage I, II and III melanosomes during melanogenesis in neoplastic and non-neoplastic melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the differential diagnosis between melanocytic proliferation and well-differentiated squamous carcinomas is not considered a challenging problem, easily resolved through morphological features and S-100/cytokeratin immunophenotype. Besides, other markers such as anti-S-100 protein, HMB-45, MITF, PNL2, and Melan-A antibodies known to react with nonmelanocytic tumors are nevertheless considered good melanoma markers [14][15][16][17]. However, review of the literature showed that only a few studies have reported on KBA.62 antibody [1,18,19].…”
Section: Introductionmentioning
confidence: 99%